Broadband linear-to-circular polarisation conversion using the diamond-shaped reflecting metasurface - Chaihongsa, Warangkana; Kuse, Ryuji; Furuya, Koichi; Phongcharoenpanich, Chuwong; Fukusako, Takeshi (My University, 2020)
To overcome the narrow axial ratio (AR) bandwidth inherent in conventional linearly to circularly polarised converters, this research proposes a metasurface (MS) with a diamond-shaped configuration that can mitigate the effect of surface wave (SW) along the MS edge and achieve a wider 3 dB AR bandwidth. The diamond-shaped MS structure is realised by slanting a square MS by 45°, and it consists of constituent unit cells of rectangular and arbitrary shapes. The rectangular unit cells are positioned 45° to the square dielectric substrate, and the unit cells along the MS edge are partially cut into arbitrary shape to be perfectly aligned along the edge. The 3 dB AR bandwidths and degradation of the MS are characterised by SW and magnetic current distribution. Simulations are carried out and an MS prototype is fabricated to verify the results. The effects of partially cut unit cells (PCUCs) along the MS edge on the SW are characterised. The simulation and measured 3 dB AR bandwidths of the diamond-shaped MS are 37.6 and 28.8%, respectively. The novelty of the proposed diamond-shaped MS polarisation converter lies in the implementation of arbitrary-shaped PCUCs and the use of the diamond-shaped configuration in place of conventional square geometry to realise wider AR bandwidth.